The unsettling of Europe : The Great Migration ,1945 to the present - Gatrell, Peter (UK: Penguin Books, 2019)
"Migration is perhaps the most pressing issue of our time, and it has completely decentered European politics in recent years. But as we consider the current refugee crisis, acclaimed historian Peter Gatrell reminds us that the history of Europe has always been one of people on the move. The end of World War II left Europe in a state of confusion with many Europeans virtually stateless. Later, as former colonial states gained national independence, colonists and their supporters migrated to often-unwelcoming metropoles. The collapse of communism in 1989 marked another fundamental turning point. Gatrell places migration at the center of post-war European history, and the aspirations of migrants themselves at the center of the story of migration. This is an urgent history that will reshape our understanding of modern Europe"--
Introduction: A European retrospective -- Forced migration in Europe-changing places -- Migrants in limbo-displaced persons in post-war Europe -- People adrift--expellees and refugees -- Rebuilding Western Europe : adventures in migration -- Building communism in Eastern Europe -- Migrants of decolonisation -- French revolution : decolonisation, migration, modernisation -- Guest workers in West Germany : migration, miracles and missing out -- Unsettling the European periphery : migration to the UK -- Migrants under communism -- A dual challenge : recession and asylum in Europe -- Unsettling Southern Europe -- "Melting pot" or "salad bowl"? : public opinion and government policy -- Migrants in Western Europe : living in a cold climate -- The end of communism : picking up the pieces -- Reunification, migration and German society -- Together in disharmony : the death of Yugoslavia -- Managing migration and asylum in the new European Union -- Privileged lives, precarious lives -- Europe, nation-states and migrants since 2008 -- Another Europe : borders, routes, migrant lives -- Belief, bodies and behaviour -- Owning the past : migration, memory, museum -- Arab Spring, European winter.
Includes bibliographical references and index.
Keywords: Immigrants -- Europe -- History; Refugees -- Europe -- History; Europe -- Emigration and immigration -- History -- 20th century; Europe -- Emigration and immigration -- History -- 21st century; Europe -- History -- 1945-